Effect of Honey Intake on Some Hematological Parameters and Testosterone, Luteinizing Hormone in Sample of Iraqi Men - Kasim, Hala Fouad; Kadhum, Yasamin Abdul Amer; Rahman, Sabah A.; Ali, Marwa Salim (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Introduction and Aim: Natural honey has many biological activities including increase Hematology (Red Blood Cell (RBC), Packed Cell Volume (PCV), Hemoglobin (Hb), Platelets (PLT) and Prothrombin time (PT)) and serum of testosterone and Luteinizing hormone. The aim of these study to know the effect of honey intake on some blood profile and to know the extent of honey impact on testosterone level. Material and Methods: About 20 healthy men were selected aged 45-60 years in Baghdad, given 50 gram Eucalyptus honey daily orally for 30 days and tested blood samples were collecting to measure the previous parameters before and after treatment. Results: The study found that there was a significant increase in all hematology parameters and testosterone hormone after eat the honey.